Modelling of temperature changes during transport of fresh fish products - Björn Margeirsson 1979- (2012)
Temperature control is a critical parameter to retard quality deterioration of perishable foodstuff, such as fresh fish, during distribution from processing to consumers. This thesis is aimed at analysing and improving the temperature management in fresh fish chill chains from processing to market by means of experiments and numerical heat transfer modelling. Ambient and product temperatures are mapped in real multi-modal distribution chains, which are both sea and air based. The results serve as a basis for simulation experiments, in which different packaging units and solutions are compared with respect to thermal insulation and product quality maintenance and more optimal ones are proposed. The experimental results are used to validate 3-D heat transfer models of fresh or superchilled whitefish, packaged in single boxes or multiple boxes assembled on a pallet, under thermal load. Much more severe temperature control problems are measured in air transport chains, especially in passenger airplanes, compared to sea transport. However, space for improvement in sea transport chains has also been discovered. The results underline the importance of precooling whitefish products before packaging for air freight and applying well distributed cooling packs inside the packaging. The results imply that product temperature differences of up to 10.5 °C can occur in a non-superchilled fresh fish pallet load and the storage life difference between the most and the least sensitive boxes on a full size pallet in a real air transport chain can exceed 1–1.5 days. It is demonstrated that even though a widely used expanded polystyrene (EPS) box design with sharp corners offers better thermal insulation than a corrugated plastic (CP) box, the sharp-corner design can be significantly improved. Such design improvement has been accomplished by developing a numerical heat transfer model in ANSYS FLUENT resulting in a new 5-kg EPS box currently manufactured by the largest EPS box manufacturer in Iceland. Other temperature-predictive ...